To fly or not to fly? An empirical study of trust, post-recovery satisfaction and loyalty of Malaysia Airlines passengers - Mohd-Any, Amrul Asraf; Mutum, Dilip S.; Ghazali, Ezlika Mohd; Mohamed-Zulkifli, Lokmanulhakim (Emerald, 2019)
Purpose: The purpose of this paper is to investigate the importance of successful service recovery in the airline sector by examining the interrelationship between perceived justice, recovery satisfaction and overall satisfaction, customer trust and customer loyalty. Furthermore, the research assesses the mediating effect of overall satisfaction and customer trust on customer loyalty. Design/methodology/approach: Data were collected via an airport intercept survey of Malaysia Airlines passengers who had experienced service failure. In total, 380 responses were used for the final analysis. The study uses partial least squares structural equation modelling technique with SmartPLS 3.0, in order to test and validate the research model and hypotheses posited. Findings: The results reveal that: recovery satisfaction is significantly affected by procedural and interactional justice; distributive and procedural justice, as well as recovery satisfaction influenced overall satisfaction; customer trust is most influenced by interactional justice, distributive justice and recovery satisfaction; customer loyalty is positively affected by customer trust, overall satisfaction and recovery satisfaction; and the influence amongst recovery satisfaction and customer loyalty is partially mediated by customer trust and overall satisfaction. Originality/value: The study contributes to a whole conceptual comprehension of the essential determinants of customer loyalty from the combined perspectives of three theories, namely, justice theory, expectancy disconfirmation theory and commitment-trust theory. This study successfully differentiates the three dimensions of perceived justice and assesses them individually to discern and compare their influence on overall satisfaction, recovery satisfaction and trust. In addition, the study finds that the influence of recovery satisfaction on loyalty is partially and sequentially mediated by trust and overall satisfaction. © 2019, Emerald Publishing Limited.